Employment of nanodiamond photocathodes on MPGD-based HEP detector at the future EIC. Issue 1 (1st November 2022) - Brunbauer, F M; Chatterjee, C; Cicala, G; Cicuttin, A; Ciliberti, P; Crespo, M L; D'Ago, D; Torre, S Dalla; Dasgupta, S; Gregori, M; Ligonzo, T; Levorato, S; et al.
Abstract : In high momenta range, the construction of a Ring Imaging CHerenkov (RICH) detector for the particle identification at the future Electron Ion Collider (EIC) is a complicated task. A compact collider setup imposes to construct a RICH with a short radiator length, hence limiting the number of photons. The number of photons can be increase by choosing to work in far UV region. However, as standard fused-silica windows are opaque below 165 nm, therefore, a windowless RICH approach could be a possible choice. In the far UV range, CsI is a widely used photo-cathode (PC) to detect photons, but because of its hygroscopic nature, it is very delicate to handle. Its Quantum Efficiency (QE) degrades in high intensity ion fluxes. These are the key reasons to search a novel, less delicate PC with sensitivity in the far UV region. Hydrogenated nanodiamond films are proposed as an alternative PC material and shown to have promising characteristics. The performance of nanodiamond PC coupled to THGEM-based detectors is the objects of our ongoing R & D. The first phase of these studies includes the characterization of THGEMs coated with nanodiamont PC, the comparison of the effective QE in vacuum and in gaseous atmospheres, the hardness respect to the PC bombardment by ions from the multiplication process. The approach is described in detail as well as all the results obtained so far with these exploratory studies.